Parental perceptions of the COVID-19 vaccine for 5- to 11-year-old children: Focus group findings from Worcester Massachusetts - Melissa Goulding; Grace W. Ryan; Princilla Minkah; Amy Borg; Maricelis Gonzalez; Nelly Medina; Pamela Suprenant; Milagros C. Rosal; Stephenie C. Lemon (Taylor & Francis Group, 2022)
Vaccine hesitancy is a long-standing public health issue. The present work describes parental perceptions of COVID-19 vaccination for 5- to 11-year-old children, to aid in vaccination efforts. Parents of 5- to 11-year-old children residing in Worcester, Massachusetts, were recruited through community partner outreach to participate in semi-structured focus groups. Focus groups were conducted via Zoom in English (n = 4) and Spanish (n = 3) with a total of 67 parents. Rapid qualitative analysis was used. Most participants were female and of Hispanic ethnicity. Themes included: (1) Trusted sources and influential types of information (e.g. personal COVID-19 vaccine stories from peers and healthcare providers), (2) Motivations for vaccination: health (i.e. protecting children, families, and communities from COVID-19), (3) Motivations for vaccination: social, emotional, and educational (i.e. mitigating related negative effects of COVID-19), (4) Drivers of vaccine hesitancy (e.g. frustration, uncertainty, and confusion), (5) Differentiating vaccine acceptance, hesitancy, and resistance, (6) Needed information. Although this context may be unique to parents of 5- to 11-year-old children from Central Massachusetts, especially those who may be Spanish-speaking, or of Hispanic ethnicity, this work reinforces the need for effective and persistent communication to combat vaccine hesitancy. In describing parents' perceptions toward COVID-19 vaccination in their 5- to 11-year-old children, we contextualize vaccine hesitancy and highlight opportunities for existing evidence-based communication strategies to increase vaccine confidence and uptake in pediatric populations.